FENOMENA DIGITALISASI PEMBAYARAN IURAN SEKOLAH DAN IMPLIKASINYA TERHADAP AKUNTABILITAS KEUANGAN SEKOLAH - Nursanita Nasution; Addin Arrahmi; Budi Wahyuni; Virna Prasamia Nugraha (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The massive influence of the Industrial Revolution 4.0 era has spread to various sectors, including the education sector. The world of education is faced with demands to adapt to the development of technology and information to improve the quality of education. The phenomenon of digitalization has now been widely applied to the payment system, including the payment of school fees. The purpose of this study is to determine the perceptions and assessments of users of digital payment systems in educational institutions, both from the side of school managers and parents of students and to analyze the implications for school financial accountability. The research method used is qualitative research with a phenomenological approach. The use of a digital payment system in school institutions can be one way to improve financial accountability, because the implementation of the system has proven to make the data generated, especially in the income cycle, more neat and accurate. This of course will have an impact on the reliability of the information generated. If the information produced is reliable, of course it will have a positive effect on financial accountability in schools.